2019
DOI: 10.1080/10942912.2019.1642354
|View full text |Cite
|
Sign up to set email alerts
|

Lipolytic degradation, water and flavor properties of low sodium dry cured beef

Abstract: The high sodium diet is harmful to the human body. In this study, beef was cured with some salt substitutes, namely SS, 39.7% NaCl, 51.3% KCl, 7% Llysine and 2% L-histidine, in order to reduce the Na content for the final products, and salt substitute effects the physicochemical, lipolytic, and flavor characteristics of dry-cured beef by determining free fatty acids, lipase activity, volatile compounds, and water mobility. The results showed that the lipase activity and unsaturated fatty acids were significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 54 publications
(83 reference statements)
0
14
0
Order By: Relevance
“… Andres et al (2005) stated that salt have a slight promoting effect on lipolysis at concentrations below 6% in production of Iberian dry-cured ham. Liu et al (2019) found that the phospholipase activities in dry-cured beef increased after treatment with a salt substitute containing l -Lys and l -His. On the other hand, there are also some researches showing that salt inhibits or slows down lipolysis phenomenon ( Jin et al, 2010 , Harkouss et al, 2015 ).…”
Section: Factors Influencing Lipolysis In Meat and Meat Productsmentioning
confidence: 99%
See 2 more Smart Citations
“… Andres et al (2005) stated that salt have a slight promoting effect on lipolysis at concentrations below 6% in production of Iberian dry-cured ham. Liu et al (2019) found that the phospholipase activities in dry-cured beef increased after treatment with a salt substitute containing l -Lys and l -His. On the other hand, there are also some researches showing that salt inhibits or slows down lipolysis phenomenon ( Jin et al, 2010 , Harkouss et al, 2015 ).…”
Section: Factors Influencing Lipolysis In Meat and Meat Productsmentioning
confidence: 99%
“…The phospholipase activity remained relatively constant, contributing to phospholipid degradation and FFA release during the curing process, but declined significantly during the smoking step. There have been attempts made in order to reduce and/or replace NaCl in cured products due to health concern of overconsumption of NaCl ( Liu et al, 2019 , Nachtigall et al, 2019 , Zhao et al, 2020 ). Substitution of NaCl by CaCl 2 at the same ionic strength enhanced lipid oxidation and lipolysis in salted meat which altered total volatile profile and shelf life of the products ( Nachtigall et al, 2019 ).…”
Section: Relationship Between Lipolysis and Lipid Oxidation In Meat A...mentioning
confidence: 99%
See 1 more Smart Citation
“…Volatile compounds were measured as described by Liu et al [18] The solid-phase microextraction device (Supelco, Bellefonte, PA) contained 50/30 μm a carboxy/polydimethylsiloxane/divinylbe (CAR/PDMS/DVB) fiber. A 5.00 g sample was placed in a 20 mL headspace bottle.…”
Section: Relative Odor Activity Valuementioning
confidence: 99%
“…Each curve represented the response of the sensor in the E-nose. [18] Each sensor had a different response intensity to the flavor, and the volatile components between SS and the control had differences. The signals of sensors S7, S9 and S2 in SS increased rapidly, and the signal of sensor S6 increased first and then decreased.…”
Section: Electronic Nosementioning
confidence: 99%